Complexity and information technologies: an ethical inquiry into human autonomous action - Quilici Gonzalez, José Artur; Broens, Mariana Cláudia [UNESP]; Quilici Ggonzalez, Maria Eunice [UNESP]; Kobayashi, Guiou (Universidade de São Paulo, Departamento de Filosofia, 2014)
In this article, we discuss, from a complex systems perspective, possible implications of the rising dependency between autonomous human social/individual action, ubiquitous computing, and artificial intelligent systems. Investigation is made of ethical and political issues related to the application of ubiquitous computing resources to autonomous decision-making processes and to the enhancement of human cognition and action. We claim that without the feedback of fellow humans, which teaches us the consequences of our actions in real everyday life, the indiscriminate use of ubiquitous computing in decision-making processes seems to be beyond the reach of any clear ethical control. We argue that the complex systems perspective may help us to foresee possible long-term consequences of our choices, in areas where human autonomous action can be directly affected by informational technologies.
Keywords: Artificial intelligent systems; Autonomous decision-making; Complex systems; Systemic compatibilism; Human enhancement; Self-organization; Ubiquitous computing